Prevalence and significance of MEFV gene mutations in a cohort of patients with rheumatoid arthritis - Koca, Suleyman Serdar; Etem, Ebru Onalan; Isik, Bahar; Yuce, Huseyin; Ozgen, Metin; Dag, Muhammet Sait; Isik, Ahmet (Elsevier France-Editions Scientifiques Medicales Elsevier, 2010)
Objectives: Pyrin/marenostrin, an inhibitory regulator of inflammation, is encoded by MEditerranean FeVer ( MEFV) gene. Mutations of this gene are the cause of familial Mediterranean fever (FMF). A connection between MEFV gene mutations and rheumatic diseases has been suggested. The aim of this study was to explore the frequency and clinical significance of MEFV gene mutations in a cohort of Turkish patients with rheumatoid arthritis ( RA). Methods: The study included 103 patients with RA and 103 age-, sex- and origin-matched healthy controls (HC). In all participants, genomic DNA was isolated and genotyped using amplification refractory mutation system or restriction fragment length polymorphism for the eight MEFV gene mutations (E148Q, M694V, M694I, M680I, V726A, A744S, R761H, and P369S). In the RA group, disease activity was determined using the disease activity score-28 (DAS-28), and radiological damage was evaluated by the modified Larsen scoring method. Results: Carrier rates of MEFV gene mutations were 26/103 (25.2%) and 24/103 (23.3%) in the RA and HC groups, respectively (p > 0.05, OR: 0.9, 95% CI: 0.48 - 1.71). In the RA group, while deformed joint count was significantly higher in the mutation carrier group than those of the non-carrier group ( p < 0.05), the level of C-reactive protein, DAS-28 and modified-Larsen scores were slightly but not significantly higher in the carrier group. Conclusion: The results of this study suggest that MEFV gene mutations appear to be an aggravating factor for the severity of RA, and consequently, patients with RA might be screened for MEFV gene mutations in countries where FMF is frequent. Whether the searching of MEFV gene mutations in RA patients is cost-effective deserves further investigations. (C) 2009 Societe francaise de rhumatologie. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Rheumatoid arthritis; MEFV gene mutations; Familial Mediterranean fever